Sneakers and The Hedonistic Dimension of Sneakers On Instagram Accounts @jejouw - Janah, Rodhotun; Lilawati, Kurnia (Pelopor Publikasi Akademika, 2024)
The purpose of this study is to find out sneakers and the hedonistic dimension of sneakers on instagram accounts @jejouw. Thrifting activities that have been rampant lately have led to the emergence of thrifting communities in Indonesia. One popular thirfting community is the Urban Sneaker Society (USS) community. This community constructs a hedonistic dimension in the younger generation through thrifting sneakers. The method used in this study is textual analysis with a case study approach on @jejouw accounts. The theory used is the theory of symbol representation referring to the theory of Stuart Hall and Roland Barthes, where this theory reviews the representation of hedonistic symbols in the use of thrifting sneakers by @jejouw. The results of this study are to show that the ownership of unique, vintage and large numbers of sneakers is a hedonistic dimension owned by @jejouw account owners to construct their masculine identity. The conclusions this masculinity is represented by using sporty sneakers. The hedonistic dimension is shown by the many types and brands of sneakers owned by @jejouw, this is because it causes fun and satisfaction to @jejouw when wearing the sneakers he owns.